A New Rhodamine B‐based Fluorescent Probe for pH Detection and Bioimaging under Strong Acidic Conditions. (7th September 2016) - Yang, Quan; Zou, Jingrong; Chirumarry, Sridhar; Huo, Chang; Tang, Linlin; Zhang, Fang; Xiang, Yi; Zuo, Hua; Shin, Dong‐Soo; Peng, Xiang
Abstract : A new pH‐sensitive rhodamine derivative was designed and synthesized using coupling reaction of rhodamine hydrazine with commercially available 3‐bromo‐4‐hydroxybenzaldehyde, and characterized via NMR, HRMS, UV and fluorescent spectra. The obtained probe was marked with yellow fluorescence under neutral condition and pink in strongly acidic media. It has high quantum yields, is not susceptible to metal interference, and has high penetration ability for cell membrane and also further applicable in bioimaging. Abstract :